1996
DOI: 10.1108/eb060673
|View full text |Cite
|
Sign up to set email alerts
|

The Deteminants of Audit Fees in HongKong: An Empirical Study

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 20 publications
(41 reference statements)
4
35
1
1
Order By: Relevance
“…Previous research pointed to possible association between audit fees and corporate profitability (Joshi & Al-Bastaki, 2000;Sandra & Patrick, 1996). Companies reported high levels of profit would disclose more information to highlight their achievements and reduce agency costs (Watts & Zimmerman, 1986).…”
Section: Profitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research pointed to possible association between audit fees and corporate profitability (Joshi & Al-Bastaki, 2000;Sandra & Patrick, 1996). Companies reported high levels of profit would disclose more information to highlight their achievements and reduce agency costs (Watts & Zimmerman, 1986).…”
Section: Profitabilitymentioning
confidence: 99%
“…A significant proportion of previous studies observed positive relationship between corporate complexity and audit fees (Simunic, 1980;Brinn et al, 1994;Cameran, 2005;Joshi & Bastaki, 2000;Clatworthy & Peel, 2006;Thinggaard & Kiertzner, 2008;Vermeer et al, 2009;Ellis & Booker, 2011;Verbruggen et al, 2011). The main reasons advanced in the literature to explain such a relationship is that greater number of subordinate financial statements require more audit time and greater expertise to ensure the accuracy of the consolidated financial statements (Sandra & Patrick, 1996). Moreover, auditing complex clients exposes external auditors to more professional liability claims than non-complex companies (Clatworthy & Peel, 2006).In the literature, corporate complexity is measured by either the complexity of operations (e.g., Taylor & Baker, 1981;Langendijk, 1997;Joshi & Al, B., 2000) or the complexity of assets reported in the balance sheet (e.g., Chan et al, 1993, Peel & Clatworthy, 2001Simunic, 1980;Francis, 1984;Francis & Stokes, 1986;Francis & Simon, 1987;Simon & Francis, 1988;Gonthier, B., & Schatt, 2007).…”
Section: Complexitymentioning
confidence: 99%
“…In an examination of audit fees for Hong Kong companies, Ho and Ng (1996) noted that companies with longer ARL appeared to pay higher audit fees. They asserted that these increased fees were due to inefficiencies in the audit process.…”
Section: Audit Firm Characteristicsmentioning
confidence: 99%
“…Among the determinants of audit fee are corporate size (Waresul & Moizer, 1996;Sandra & Patrick, 1993;Kamal & Rana, 2008), status of the audit firm (big 4 or non-big 4) (Waresul & Moizer, 1996;Kamal & Rana, 2008), industry type (Mohd & Takiah, 1993;Kamal & Rana, 2008;Leventis, Hassan & Dedoulis, 2013;Casterella, Desir & Irwin, 2013), degree of corporate complexity (Sandra & Patrick, 1993;Kamal & Rana, 2008;Sundgren & Svanstrom, 2013), perceived risk (Sandra & Patrick, 1993;Mark et al, 2007;Kamal & Rana, 2008;Aswadi et al, 2009;Kim & Fukukawa, 2012), ownership concentration (Aswadi et al, 2009), type of equity ownership (Badertscher et al, 2013) and audit delay (Sandra & Patrick, 1993;Coster, Dahl & Jenson, 2013). In addition, Taylor & Simon (1999) found that higher audit fee is associated to litigation propensity, higher level of disclosure (and stringent regulation while Stanley (2011) finds that audit fees reflects future changes in client earnings.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The selection of control variables in model was mainly based on the extensive past literature such of Waresul & Moizer (1996), Sandra & Patrick (1993), Kamal & Rana (2008), Mark et al (2007) and also an adaptation from the study of Lin & Liu (2009).…”
Section: H1mentioning
confidence: 99%